BOOK REVIEW: SOCIAL LEADERSHIP IN EARLY CHILDHOOD EDUCATION AND CARE: AN INTRODUCTION - Dey, Manna (LLT Journal: A Journal on Language and Language Teaching, 2024)
Social leadership in early childhood education and care refers to the ability of educators to guide and promote positive social behaviors in young children, as well as create a supportive learning environment that fosters cooperation and empathy. It involves using a range of strategies and techniques to help children develop social skills, self-regulation, and emotional intelligence. Social leadership in early childhood education and care is an essential factor in supporting positive social and emotional development in young children in the UK. According to a study by Breslin and colleagues (2019), effective social leadership involves creating a supportive and inclusive learning environment, promoting positive social behaviors, and using evidence-based strategies to help children develop social skills and emotional intelligence. The study emphasizes the importance of social leadership in improving children’s academic and social outcomes, as well as their long-term well-being. Moreover, the research suggests that social leadership can be especially beneficial in supporting the development of children from disadvantaged backgrounds.